2009
DOI: 10.1002/zaac.200900050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure and Ionic Conductivity of Ag8I2(CrO4)3

Abstract: Ag 8 I 2 (CrO 4 ) 3 has been synthesized by solid state reaction, starting from stoichiometric mixtures of Ag 2 O, AgI and Cr 2 O 3 , at elevated oxygen pressures. The compound crystallizes in the hexagonal space group P6 3 /m, with the unit cell dimensions a = 9.4474(4) Å, c = 10.2672(4) Å, γ = 120°, V = 793.61(6) Å 3 , and Z = 6. The crystal structure was solved by direct methods and refined, basing on single crystal diffraction data (815 independent reflections, R1 = 2.45 %). The structure is fully ordered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The crystal structures of quaternary inorganic compounds composed of silver and iodide ions and oxyanionic groups, such as Ag 2 I(NO 3 ) 2 (Birnstock & Britton, 1970), Ag 16 I 12 P 2 O 7 (Garrett et al, 1982), Ag 5 IP 2 O 7 (Adams & Preusser, 1999), Ag 4 IPO 4 (Oleneva et al, 2008), Ag 8 (CrO 4 ) 3 I 2 (Pitzschke et al, 2009b), Ag 9 (GeO 4 ) 2 I (Pitzschke et al, 2009c), Ag 8 I 4 V 2 O 7 (Adams, 1996), Ag 13 (AsO 4 ) 3 I 4 (Pitzschke et al, 2009a), Ag 4 I 2 SeO 4 (Pitzschke et al, 2008a), Ag 3 ITeO 4 (Pitzschke et al, 2008a), Ag 9 I 3 (IO 3 ) 2 (SeO 4 ) 2 (Pitzschke et al, 2008b) and Ag 26 I 18 (WO 4 ) 4 (Chan & Geller, 1977) have been reported.…”
Section: Database Surveymentioning
confidence: 99%
“…The crystal structures of quaternary inorganic compounds composed of silver and iodide ions and oxyanionic groups, such as Ag 2 I(NO 3 ) 2 (Birnstock & Britton, 1970), Ag 16 I 12 P 2 O 7 (Garrett et al, 1982), Ag 5 IP 2 O 7 (Adams & Preusser, 1999), Ag 4 IPO 4 (Oleneva et al, 2008), Ag 8 (CrO 4 ) 3 I 2 (Pitzschke et al, 2009b), Ag 9 (GeO 4 ) 2 I (Pitzschke et al, 2009c), Ag 8 I 4 V 2 O 7 (Adams, 1996), Ag 13 (AsO 4 ) 3 I 4 (Pitzschke et al, 2009a), Ag 4 I 2 SeO 4 (Pitzschke et al, 2008a), Ag 3 ITeO 4 (Pitzschke et al, 2008a), Ag 9 I 3 (IO 3 ) 2 (SeO 4 ) 2 (Pitzschke et al, 2008b) and Ag 26 I 18 (WO 4 ) 4 (Chan & Geller, 1977) have been reported.…”
Section: Database Surveymentioning
confidence: 99%
“…Silver(I) chalcogenide halides like Ag 3 S X (with X = Br, I), Ag 5 Te 2 Cl, or Ag 19 Te 6 Br 7 , and silver(I) polychalcogenide halides like Ag 10 Te 4 Br 3 , Ag 23 Te 12 X ( X = Cl, Br), , or Ag 20 Te 10 BrI are mixed conducting materials with a high ion conductivity comparable with related compounds like Ag 7 Fe 3 ( X 2 O 7 ) 4 with ( X = P, As), Ag 8 I 2 (CrO 4 ) 3 , Ag 4 I 2 SeO 4 , or Ag 3 ITeO 4 in this field. Although all the above-mentioned polychalcogenides contain anionic structure units, capable of performing a Peierls-distortion in the solid state, the chalcogenide halides do not fulfill the structural requirements for such a partial covalent bonding in the anion substructure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rapid decomposition of the material in the presence of moisture makes its use as a substrate material impractical. Several silver oxyacid based compounds of the form AgI x (Ag y MO z ) 1− x where M = P, As, Se, Te, Cr, Mo, and W have been found to be ionic conductors and are significantly less reactive to moisture compared to RbAg 4 I 5 . In particular, the structure and tunability of the glass transition, activation energy, and ionic conductivity of (AgI) x (AgPO 3 ) 1− x glass mixtures have been well studied due to the wide transparent glass forming region from x = 0 to 0.6 .…”
Section: Introductionmentioning
confidence: 99%